What do we know about how children and adolescents conceptualise violence? A systematic review and meta-synthesis of qualitative studies from sub-Saharan Africa. - Ellen Turner; Susan A Kelly; Emily Eldred; Katrina Bouzanis; Anne Gatuguta; Manuela Balliet; Shelley Lees; Karen Devries (PLoS ONE)
Background Half of the world's children experience violence every year, but the meaning of violence is not universally agreed. We may therefore risk failing to measure, and address, the acts that matter most to children and adolescents. In this paper, we describe and synthesise evidence on how children and adolescents in sub-Saharan Africa conceptualise different behavioural acts which are deemed violence in childhood under WHO and UN CRC definitions. Methods and findings We conducted a systematic review of qualitative studies. We searched PsychINFO, CINAHL, Embase, Global Health, Medline and ERIC for all publications released prior to March 2023. 30 papers met inclusion criteria. We synthesised primary data from children and adolescents and drew upon theoretical and contextual interpretations of authors of included studies. Only 12 of more than 45 sub-Saharan African countries were represented with relevant research. Of the 30 included papers, 25 came from three countries: South Africa, Uganda and Ghana. Only 10 of 30 papers reported data from young children (pre-adolescence), and 18 of 30 papers primarily focused on sexual violence. 14 studies used child friendly and/or participatory methods. From this limited evidence, we identified six overarching themes in how children and adolescents conceptualised their experiences of acts internationally recognised as violence: 1) adults abusing or neglecting responsibility; 2) sexual violence from peers, family and community members; 3) violence in established intimate relationships; 4) emotional violence surrounding sex from peers and community members; 5) fighting and beating between peers; 6) street and community dangers. No studies meeting our inclusion criteria specifically examined children or adolescents' conceptualisations of homophobic or transphobic violence; violence against children with disabilities; boys' experiences of sexual violence from male perpetrators; trafficking, modern slavery or conflict; child labour; or female genital mutilation. We found that three dimensions were important in how children and adolescents constructed conceptualisations of violence: their age, relationship to the perpetrator, and the physical location of acts they had experienced. These dimensions were interrelated and gendered. Conclusion The current limited evidence base suggests children and adolescents' conceptualisations of violence overlapped with, but were also distinct from, the WHO and UNCRC definitions of violence. Currently international survey tools focus on measuring types and frequencies of particular acts and neglect to focus on children's understandings of those acts. Relationship to perpetrator, age of child, physical location are all important in how children conceptualise their experiences of acts internationally recognised as violence, and therefore might be important for their health and social outcomes. Those developing measures should account for these dimensions when developing items for testing.